2014
DOI: 10.1007/s00253-014-5542-9
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic synthesis of model substrates recognized by glucuronoyl esterases from Podospora anserina and Myceliophthora thermophila

Abstract: Glucuronoyl esterases (GEs) are recently discovered enzymes that are suggested to cleave the ester bond between lignin alcohols and xylan-bound 4-O-methyl-D-glucuronic acid. Although their potential use for enhanced enzymatic biomass degradation and synthesis of valuable chemicals renders them attractive research targets for biotechnological applications, the difficulty to purify natural fractions of lignin-carbohydrate complexes hampers the characterization of fungal GEs. In this work, we report the synthesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 33 publications
2
27
0
5
Order By: Relevance
“…These sequences are strongly conserved in all GE sequences, suggesting again the importance of these residues as the components of catalytic triad. In support of our proposal, the crystal structures of Cip2 and StGE (Charavgi et al, 2013;Pokkuluri et al, 2011) showed that the disulfide bond is formed between the cysteine residues equivalent to Cys304 and Cys440 in NcGE that links the consensus sequences VTGCSRXGKGA and HC, hence bringing serine and histidine residues close together in the catalytic site (Charavgi et al, 2013;Katsimpouras et al, 2014). Cys336 involved in another disulfide bond with Cys412 is near E328 and both of these residues are also highly conserved, possibly assisting in introducing glutamic acid to create the catalytic triad.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…These sequences are strongly conserved in all GE sequences, suggesting again the importance of these residues as the components of catalytic triad. In support of our proposal, the crystal structures of Cip2 and StGE (Charavgi et al, 2013;Pokkuluri et al, 2011) showed that the disulfide bond is formed between the cysteine residues equivalent to Cys304 and Cys440 in NcGE that links the consensus sequences VTGCSRXGKGA and HC, hence bringing serine and histidine residues close together in the catalytic site (Charavgi et al, 2013;Katsimpouras et al, 2014). Cys336 involved in another disulfide bond with Cys412 is near E328 and both of these residues are also highly conserved, possibly assisting in introducing glutamic acid to create the catalytic triad.…”
Section: Discussionmentioning
confidence: 61%
“…Besides, based on the crystal structures of Cip2 (Pokkuluri et al, 2011) and StGE2 (Charavgi et al, 2013), the catalytic triad of GEs was suggested to be composed of two more amino acids, glutamic acid and histidine, located Cterminal to the nucleophile serine. The molecular docking study of StGE2 with the model substrate (Katsimpouras et al, 2014) also supported this idea, which led to the hypothesis that Ser-Glu-His is the standard catalytic triad for GEs. Taking these into consideration, we propose two more consensus sequences constituting the catalytic triad of GEs: PQESG and HC containing the glutamic acid and histidine residues (underlined; position 328 and 439 in NcGE, respectively).…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…To complete the set of enzymes required for complete degradation of hemicelluloses, two CE members were studied. The methyl glucuronoyl esterase from family CE15 was able to cleave the ester bond between lignin alcohols and xylan-bound 4-O-methyl-D-glucuronic acid (Katsimpouras et al, 2014). The acetyl esterase from family CE16 was versatile in terms of activity on xylan.…”
Section: Hemicellulasesmentioning
confidence: 99%
“…GEs not only appear to be inducible constituents of plant cell wall-degrading enzyme systems but also are frequently constituents of bi-or multimodular enzymes. Some of them, such as GE from T. reesei and Podospora anserina, contain a family 1 carbohydrate binding module, CBM1 (6,13). Phanerochaete chrysosporium produces two forms, one without and one with the CBM1 module (12).…”
mentioning
confidence: 99%